2011
DOI: 10.1542/peds.2010-2026
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient Health Care Utilization for Children Dependent on Long-term Mechanical Ventilation

Abstract: Discharges for children associated with LTMV require substantively greater inpatient resource use than other children with CCCs. As the number of discharges and associated aggregate charges increase over time, additional research must examine patterns of care for specific clinical subgroups of LTMV, especially children aged 4 years and younger.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 98 publications
(97 citation statements)
references
References 25 publications
4
92
0
1
Order By: Relevance
“…35,36 Although no other studies have addressed the rehospitalization rates for children with tracheostomy, before and after decannulation, several have found that children who are ventilator dependent at home have a higher risk of rehospitalization than other children. 11,12,[36][37][38][39] The decrease in readmission rate after decannulation may be secondary to removal of the tracheostomy, improvement in BPD, or both.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35,36 Although no other studies have addressed the rehospitalization rates for children with tracheostomy, before and after decannulation, several have found that children who are ventilator dependent at home have a higher risk of rehospitalization than other children. 11,12,[36][37][38][39] The decrease in readmission rate after decannulation may be secondary to removal of the tracheostomy, improvement in BPD, or both.…”
Section: Discussionmentioning
confidence: 99%
“…11 In addition, the rate of hospital discharges for all children dependent on long-term mechanical ventilation increased 55% from 2000 to 2006. 12 The respiratory outcomes of patients with BPD range from no oxygen requirement to chronic ventilator dependency. Various publications [13][14][15] address the outcome of the least severe types of BPD, yet very limited data exist on BPDrelated chronic respiratory failure.…”
mentioning
confidence: 99%
“…This definition of operative mortality is particularly relevant to our study population, since patients with tracheostomy after cardiac surgery often are transferred for ongoing care to either secondary acute care or rehabilitation facilities. [6,11]. We Table 1, and the 10 most common primary cardiac diagnoses and index cardiac surgical procedures performed are listed in Table 2.…”
Section: Data Collection and Definitionsmentioning
confidence: 99%
“…Benneyworth et al 15 estimated the prevalence to be 6 -14 per 100,000 children. In terms of in-patient admissions, the rate is estimated to be 174 per 100,000 non-newborn pediatric discharges.…”
Section: Trends and Outcomesmentioning
confidence: 99%